An Exploratory Study of the Relationship between Defensive and Supportive Talk, Verbal Aggressiveness and Communication Climate - Hajdasz, Peter A. (Université d'Ottawa / University of Ottawa, 2012)
Significant research has investigated Jack Gibb’s model of defensive and supportive communication, but little has explored the influence of the type of talk -- defensive or supportive -- on perceptions of communication climate and the role that verbal aggressiveness may play in influencing both the types of talk and these perceptions. This thesis explored the relationship between defensive and supportive talk, verbal aggressiveness and communication climate using a mixed-method approach. Specifically, the Verbal Aggressiveness Scale was used to group participants for a dyadic problem solving exercise which generated conversational data that was analyzed qualitatively. Then, the Communication Climate Inventory was used to measure participants’ perceptions of the communication climate that emerged in their problem-solving dyad. The findings highlight factors that may influence the perception of communication climate. Examples of supportive talk that builds positive communication climates and limits the effects of verbal aggressiveness and examples of defensive talk that leads to negative communication climates are provided. This research demonstrates that language has an influence on communication climate through the words that shape the complex ways people perceive and understand each other and, interestingly, that the negative impact of defensive communication overrides the positive impact of supportive communication on the emergent communication climate.
Keywords: Communication Climate; Verbal Aggressiveness; Mixed-Method Research Design; Defensive Communication; Supportive Communication